Preparation method and application of microalgae exosome-fucoxanthin composite nanoparticles

By loading fucoxanthin into microalgae exosomes to form composite nanoparticles, the problems of poor stability and low bioavailability of fucoxanthin are solved, and the effect of improving its stability and bioavailability is achieved.

CN119606919AActive Publication Date: 2025-03-14NINGBO UNIV
View PDF 14 Cites 0 Cited by

Patent Information

Application Number
CN202510152785.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-12
Publication Date
2025-03-14
Estimated Expiration
2045-02-12

AI Technical Summary

Technical Problem

The highly unsaturated structure of fucoxanthin leads to poor stability and low water solubility, which limits its bioavailability and effective concentration in the body, which in turn affects its application in treatment and health care.

Method used

By loading fucoxanthin into microalgae exosomes, fucoxanthin is embedded in the lipid bilayer structure of microalgae exosomes by electroporation technology to form microalgae exosome-fucotylate complex nanoparticles.

Benefits of technology

This method improves the stability and bioavailability of fucoxanthin, enhances its antioxidant activity, prolongs its stability under light, heat and storage conditions, and thus improves its therapeutic effect in vivo.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119606919A_ABST
    Figure CN119606919A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of microalgae exosome-fucoxanthin composite nanoparticles, and the preparation method is characterized by comprising the following steps: adding a fucoxanthin ethanol solution and a microalgae exosome solution into a cuvette according to a mass ratio of (0.5-1.5): 1, co-incubating for 30 minutes, adding an electrotransfection buffer solution which is 1-3 times of the volume of the mixed solution, and uniformly stirring; the mixed solution in the cuvette is subjected to electroporation by using an electroporation instrument, electric shock is carried out by controlling the voltage to be 100-500 V and the capacitance to be 300-700 [mu] F, then incubation is carried out for 0.5-2 h at the temperature of 35-40 DEG C, the mixed solution is centrifuged for 20-40 min under the conditions of 80000-120000 g and the temperature of 4 DEG C, precipitation particles are collected, and the microalgae exosome-fucoxanthin composite nanoparticles are obtained. The application of the composite nanoparticle in preparation of an antioxidant, an ABTS free radical scavenger and / or a DPPH free radical scavenger has the advantages that the stability and bioavailability of fucoxanthin are improved, and a synergistic antioxidant effect is generated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of biotechnology, and specifically relates to a preparation method and application of microalgae exosome-fucoxanthin composite nanoparticles. Background Art

[0002] Fucoxanthin (FX) is a fat-soluble natural xanthophyll carotenoid that can be widely isolated from marine brown algae and other large or micro algae. It has a wide range of bioavailability and functions, such as significant antioxidant, anti-obesity, anti-diabetic and anti-inflammatory properties, and has important application potential in the treatment and prevention of various cancers and tumors.

[0003] The highly unsaturated conjugated double bonds, olefin bonds and epoxy structures in the chemical structure of fucoxanthin make it poorly stable, and it is easy to undergo structural changes when exposed to heat, light and gastric acid, affecting its bioavailability. In daily processing, storage and use, fucoxanthin is very sensitive to temperature and light. High temperature will destroy the molecular structure of fucoxanthin, resulting in double bond breakage or isomerization. As the temperature rises, its degradation will accelerate. Ultraviolet and visible light irradiation will cause the abundant conjugated double bonds in its molecular structure to undergo photochemical oxidation, isomerization and degradation reactions, significantly reducing the biological activity and stability of fucoxanthin. The gastric acid environment will also affect its structure, resulting in structural changes, limiting its application in drug development and food industry. At the same time, the dual problems of poor stability and low water solubility directly lead to its low bioavailability, which is not conducive to its absorption, distribution and metabolism in the body, and cannot give full play to its potential bioavailability, resulting in its low effective concentration in the body, and cannot achieve the expected therapeutic or health care effects. In addition, there are many challenges in developing oral dietary products, such as the difficulty in achieving the desired effect in dosage form design and drug release control. In summary, the market prospects of fucoxanthin are very broad, but due to its highly unsaturated structure, it has defects such as poor water solubility and strong environmental sensitivity, which greatly limit the actual production and application of fucoxanthin functional drugs. Therefore, the development of an effective delivery system can reduce the instability of fucoxanthin under adverse conditions, thereby improving its oral bioavailability.

[0004] Extracellular vesicles (EVs) are natural membrane-like nanoparticles with a diameter of 30-150nm that are naturally released by cells. They have a typical structure that is round and partially concave, resembling a "tray". EVs are secreted by cells and can carry a variety of substances such as nucleic acids, proteins, amino acids, lipids, etc. According to size, composition, subcellular origin and secretion mode, extracellular vesicles can be divided into the following three types: exosomes, microvesicles and apoptotic bodies. After being released by cells, exosomes can participate in the regulation of various physiological activities, such as development, immunity, tissue homeostasis, cancer and neurodegenerative diseases, and play an important role in intercellular communication under physiological and pathological conditions. Due to their unique phospholipid bilayer structure, exosomes can embed or adsorb various drugs and encapsulate different types of drugs in their inner cavity. These exosomes have become an ideal drug delivery tool due to their natural biocompatibility, low immunogenicity, potential cancer cell targeting properties and enhanced cell uptake efficiency by direct fusion with the plasma membrane.

[0005] Chlorella ( Chlorella ) is a single-cell freshwater microalgae of the genus Chlorella in the Chlorophyta, which has the characteristics of fast growth, short reproduction cycle and easy artificial cultivation. As an important source of water plants, microalgae are easy to culture on a large scale, have low culture costs and are rich in active substances. They show great advantages in drug delivery, tumor treatment, wound healing, etc., and can produce exosomes more quickly and easily. There are no related research reports on the use of microalgae exosomes to embed fucoxanthin drug delivery systems. Summary of the invention

[0006] The technical problem to be solved by the present invention is to provide a method for preparing microalgae exosome-fucoxanthin composite nanoparticles which improves the stability and bioavailability of fucoxanthin and produces a synergistic antioxidant effect and its application.

[0007] The technical solution adopted by the present invention to solve the above technical problems is: a method for preparing microalgae exosome-fucoxanthin composite nanoparticles, comprising the following steps: adding fucoxanthin ethanol solution and microalgae exosome solution in a mass ratio of 0.5-1.5:1 to a cuvette and incubating for 30 minutes, adding 1-3 times the volume of the mixed solution of electrotransfer buffer, and then using an electroporator to electroporate the mixed solution in the cuvette, controlling the voltage to 100-500V and the capacitance to 300-700μF for electric shock, and then incubating at 35-40°C for 0.5-2h, the mixed solution is centrifuged at 80000-120000g, 4°C for 20-40min, and the precipitated particles are collected to obtain microalgae exosome-fucoxanthin composite nanoparticles.

[0008] Furthermore, the preparation method of the fucoxanthin ethanol solution is as follows: dissolve fucoxanthin in 95% ethanol, stir with a magnetic stirrer to completely dissolve it, and obtain a fucoxanthin ethanol solution with a concentration of 5 mg / mL.

[0009] Furthermore, the preparation method of the microalgae exosome solution is as follows: the cultured Chlorella algae solution is centrifuged at 200-400g for 8-12min, 1500-2500g for 15-25min, and 8,000-12000g for 25-35min at 4°C by differential centrifugation to remove cells and cell debris, the supernatant is filtered through a 0.22μm water filter membrane and then ultracentrifuged at 80,000-1200,000g for 80-100min, the precipitate is resuspended in sterile PBS buffer to obtain a microalgae exosome solution with a final protein concentration of 1 mg / mL.

[0010] Furthermore, the Chlorella is cultured in an autotrophic mode, specifically as follows: a single colony of Chlorella spFACHB-9 is inoculated into 200 mL of BG11 culture medium and cultured in a shaker at 25°C and 120 rpm for 6-8 days, then the seed liquid is continuously inoculated into 600 mL of BG11 culture medium and cultured in a shaker at 25°C and 120 rpm for 5-6 days, and the Chlorella FACHB-9 algae liquid is collected, wherein the formula of the BG11 culture medium is as follows: 1.5 g NaNO3, 0.04 g K2HPO4, 0.075 g MgSO4·7H2O, 0.036 g CaCl2·2H2O, 0.02 g Na2CO3, 0.006 g citric acid, 0.006 g ferric citrate, 1 mL of trace element solution A5 and 1000 mL of distilled water. The formula of trace element solution A5 is: H3BO3 2.86g / L, MnCl2·4H2O 1.81g / L, ZnSO40.222g / L, Na2MoO4 0.39g / L, CuSO4·5H2O 0.079g / L, Co (NO3)2·6H2O 0.049g / L.

[0011] Furthermore, the Chlorella is cultured in a polyculture mode, specifically as follows: Chlorella sp FACHB-9 The seed solution was inoculated into 200 mL of BG11 medium containing 2 g / L glucose and cultured in a shaker at 25°C and 120 rpm for 6-8 days. The seed solution was then inoculated into 600 mL of BG11 medium containing 2 g / L glucose and cultured in a shaker at 25°C and 120 rpm for 5-6 days to collect the Chlorella FACHB-9 algae solution.

[0012] Furthermore, the chlorella is cultured in a heterotrophic mode, specifically as follows: Chlorella sp FACHB-9 The seed solution was inoculated into 200 mL of modified Endo medium and cultured in a shaker at 25°C and 120 rpm for 6-8 days, and then the seed solution was continuously inoculated into 600 mL of modified Endo medium and cultured in a shaker at 25°C and 120 rpm for 5-6 days, and the algae solution of Chlorella FACHB-9 was collected. The formula of the modified Endo medium is as follows: 28 g / L glucose, 1.2 g / L potassium dihydrogen phosphate, 4.8 g / L urea, 1.2 g / L magnesium sulfate, 105 mg / L calcium chloride dihydrate, 16 g / L ferrous sulfate heptahydrate, 2.1 mg / L disodium ethylenediaminetetraacetic acid, 0.2 g / L trisodium citrate, 2.86 mg / L boric acid, 0.222 mg / L zinc sulfate heptahydrate, 1.81 mg / L manganese chloride tetrahydrate, 0.025 mg / L sodium molybdate, 0.07 mg / L copper sulfate pentahydrate and 1.2 mg / L cobalt nitrate hexahydrate.

[0013] Furthermore, the formula of the electrotransfer buffer is as follows: 1.15 mM potassium dihydrogen phosphate, 25 mM potassium chloride, 1.46 M sucrose, pH 7.2.

[0014] Furthermore, the mass ratio of the fucoxanthin ethanol solution to the microalgae exosome solution is 1:1.

[0015] The present invention also provides the use of microalgae exosome-fucoxanthin composite nanoparticles prepared by the above method in the preparation of antioxidants.

[0016] The present invention also provides the use of the microalgae exosome-fucoxanthin composite nanoparticles prepared by the above method in the preparation of 2,2'-azino-bis-3-ethylbenzothiazoline-6-sulfonic acid (ABTS) free radical scavenger and / or 1,1-diphenyl-2-trinitrophenylhydrazine (DPPH) free radical scavenger.

[0017] Compared with the prior art, the advantages of the present invention are as follows: the present invention discloses for the first time a preparation method and application of microalgae exosome-fucoxanthin composite nanoparticles. The method selects Chlorella vulgaris as the algae beads with high exosome production in heterotrophic mode, and then extracts exosomes by combining differential centrifugation and ultracentrifugation. Chlorella vulgaris exosomes are used as wall materials and fucoxanthin is used as core materials. Fucoxanthin is loaded into heterotrophic Chlorella vulgaris exosomes by electroporation. The conjugated double bond system in the chemical structure of fucoxanthin itself makes it susceptible to oxidation and loses its activity. The encapsulation of exosomes can reduce the damage of these adverse factors to fucoxanthin, thereby maintaining its structural integrity and maintaining its antioxidant activity before reaching the site of action, thereby possibly enhancing its ability to exert antioxidant effects in vivo. In addition, when microalgae exosomes act together with fucoxanthin, a synergistic antioxidant effect may be produced to improve the stability and bioavailability of fucoxanthin. The invention is simple and convenient to operate, low in cost, short in production cycle, and suitable for batch processing and industrialization. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 The growth curves of Chlorella FACHB-9 in Example 1 under autotrophic, polytrophic and heterotrophic modes; Figure 2 The protein concentration of exosomes extracted from Chlorella FACHB-9 in autotrophic, mixed and heterotrophic modes in Example 1; Figure 3 This is a TEM electron micrograph of exosomes extracted from Chlorella FACHB-9 under heterotrophic mode in Example 2; Figure 4 is the fucoxanthin loading rate in the Chlorella exosome-fucoxanthin composite nanoparticles under the electric shock of different voltages and capacitances in Example 3; Figure 5 This is a TEM electron microscope image of Chlorella exosome-fucoxanthin composite nanoparticles in Example 4; Figure 6 The particle size and Zeta potential diagram of Chlorella exosomes and Chlorella exosome-fucoxanthin composite nanoparticles under three culture modes in Example 4; Figure 7 The results of drug loading rate, embedding rate, protein recovery rate and FX loss rate of microalgae exosome-fucoxanthin composite nanoparticles in Example 5; Figure 8 are the stability test results of the microalgae exosome-fucoxanthin composite nanoparticles in Example 6, wherein a is the effect of ultraviolet light irradiation time on the stability of fucoxanthin in different samples, b is the effect of heating time at 60° C. on the retention rate of fucoxanthin in different samples, and c is the effect of storage time at room temperature on the retention rate of fucoxanthin in different samples; Fig. 9The antioxidant test results of different samples in Example 7, wherein a is the ABTS clearance rate of different samples, and b is the DPPH clearance rate of different samples. DETAILED DESCRIPTION

[0019] The present invention is further described in detail below with reference to the accompanying drawings.

[0020] Example 1: Screening of a culture model for producing high exosomes of Chlorella.

[0021] Chlorella autotrophic mode: a single colony of Chlorella sp FACHB-9 was inoculated into 200 mL BG11 medium and cultured in a shaker at 25°C and 120 rpm for 6-8 days, and then the seed solution was inoculated into 600 mL BG11 medium and cultured in a shaker at 25°C and 120 rpm for 5-6 days, and the Chlorella FACHB-9 algae solution was collected. The formula of BG11 medium is as follows: NaNO3 1.5g, K2HPO4 0.04g, MgSO4·7H2O 0.075g, CaCl2·2H2O 0.036g, Na2CO3 0.02g, citric acid 0.006g, ferric citrate 0.006g, trace element solution A5 1mL and distilled water 1000mL. The formula of trace element solution A5 is: H3BO3 2.86g / L, MnCl2·4H2O 1.81g / L, ZnSO4 0.222g / L, Na2MoO4 0.39g / L, CuSO4·5H2O 0.079g / L, Co (NO3)2·6H2O 0.049g / L.

[0022] Chlorella polyculture model: the single algae colony Chlorella sp FACHB-9 The seed solution was inoculated into 200 mL of BG11 medium containing 2 g / L glucose and cultured in a shaker at 25°C and 120 rpm for 6-8 days. The seed solution was then inoculated into 600 mL of BG11 medium containing 2 g / L glucose and cultured in a shaker at 25°C and 120 rpm for 5-6 days to collect the Chlorella FACHB-9 algae solution.

[0023] Heterotrophic mode of Chlorella: the single algae colony Chlorella sp FACHB-9The seed solution was inoculated into 200 mL of modified Endo medium and cultured in a shaker at 25°C and 120 rpm for 6-8 days, and then the seed solution was continuously inoculated into 600 mL of modified Endo medium and cultured in a shaker at 25°C and 120 rpm for 5-6 days, and the algae solution of Chlorella FACHB-9 was collected. The formula of the modified Endo medium is as follows: 28 g / L glucose, 1.2 g / L potassium dihydrogen phosphate, 4.8 g / L urea, 1.2 g / L magnesium sulfate, 105 mg / L calcium chloride dihydrate, 16 g / L ferrous sulfate heptahydrate, 2.1 mg / L disodium ethylenediaminetetraacetic acid, 0.2 g / L trisodium citrate, 2.86 mg / L boric acid, 0.222 mg / L zinc sulfate heptahydrate, 1.81 mg / L manganese chloride tetrahydrate, 0.025 mg / L sodium molybdate, 0.07 mg / L copper sulfate pentahydrate and 1.2 mg / L cobalt nitrate hexahydrate.

[0024] Biomass determination method: Take 10mL of Chlorella FACHB-9 algae liquid obtained under different culture modes, filter through 0.45μm water filter membrane respectively, take the retentate and dry it in an oven at 85℃ and weigh it after 24 hours, subtract the weight of 0.45μm water filter membrane from the dried weight to get the biomass of the algae liquid obtained under different culture modes.

[0025] Extraction method of exosomes from algal fluid: 800 mL of FACHB-9 algal fluid obtained under different culture modes was collected and centrifuged at 300 g for 10 min, 2,000 g for 20 min, and 10,000 g for 30 min at 4 °C by differential centrifugation to remove cells and cell debris. The supernatant was filtered through a 0.22 μm water filter and then ultracentrifuged at 100,000 g for 90 min. The precipitate was resuspended in 2 mL of sterile PBS buffer to obtain an exosome suspension, which was stored at -80 °C for subsequent experiments.

[0026] Protein concentration determination method: Take 100 μL of exosome suspension extracted from algae in different culture modes and add 100 μL lysis buffer at a volume ratio of 1:1, sonicate 3 times for 10 seconds and then stand on ice for 30 minutes. The lysis buffer formula is as follows: 50 mM Tris-HCl (pH 7.4 - 8.0), 1% Triton X-100, 10% sodium deoxycholate, 1 mM phenylmethylsulfonyl fluoride, 1 mM ethylenediaminetetraacetic acid.

[0027] 20 μL of different sample lysates were taken into a 96-well ELISA plate, and 200 μL BCA working solution (MA0082-2, Meilun Biotechnology) was added to each well. The plates were placed at 37°C for 30 min, and the sample absorbance at 562 nm was measured using an ELISA instrument. The exosome protein concentration was calculated based on the linear relationship between the absorbance value after subtracting the blank control and the exosome protein concentration.

[0028] Figure 1 The growth curves of Chlorella FACHB-9 under autotrophic, mixed and heterotrophic modes are shown in Figure 2. Figure 1 It can be seen that under the heterotrophic mode, the biomass of Chlorella FACHB-9 reached its maximum on the tenth day, which was 1.64±0.06 g / L, which was 2.51 times and 1.33 times that of autotrophy and mixed culture, respectively. This shows that the biomass of Chlorella FACHB-9 under the heterotrophic mode was significantly higher than that of the other two culture modes.

[0029] Figure 2 The concentration of exosome protein extracted from the algae liquid of Chlorella vulgaris FACHB-9 under autotrophic, mixed and heterotrophic modes was determined by the BCA method. Figure 2 It can be seen that the concentration of Chlorella exosomes extracted under heterotrophic mode is 1.87±0.08 mg / g dry weight of algae, which is 3.01 and 1.76 times that of autotrophy and mixed culture, respectively, indicating that the protein concentration of Chlorella FACHB-9 extracted under heterotrophic mode is significantly higher than the biomass of the other two modes.

[0030] The above results indicate that Chlorella FACHB-9 cultured in heterotrophic mode has relatively higher biomass and exosomes with higher protein concentration, so Chlorella FACHB-9 cultured in heterotrophic mode was selected for subsequent experiments.

[0031] Example 2: Structural characterization of exosomes extracted from Chlorella cultured in heterotrophic mode.

[0032] Transmission electron microscopy (TEM) determination: A JEM-2100 transmission electron microscope was used to observe the morphological structure of the exosomes of Chlorella FACHB-9 under heterotrophic mode. The exosome suspension extracted from the algae liquid cultured under heterotrophic mode in Example 1 was dripped onto the carbon-coated copper grid, and the excess sample was removed with filter paper after standing at room temperature for 10 minutes. The copper grid was then stained with phosphotungstic acid for 10 seconds, and the excess liquid was removed with filter paper. The excess liquid was removed with filter paper after washing with PBS buffer for 1 minute, and dried under an incandescent lamp. The morphology of the newly prepared sample was observed using a transmission electron microscope. Figure 3 This is a transmission electron micrograph of the exosomes of Chlorella FACHB-9 under heterotrophic mode. Figure 3As shown, the Chlorella FACHB-9 exosomes have a typical "tray"-shaped structure that is round and partially concave, and have a lipid bilayer structure, which is consistent with the conventional exosome structure.

[0033] Example 3: A method for preparing fucoxanthin nanoparticles using microalgae exosomes, comprising the following steps: Step 1, dissolve 5 mg of fucoxanthin in 1 mL of 95% ethanol, stir with a magnetic stirrer at 800 rpm for 2 h to completely dissolve it, and obtain a 5 mg / mL fucoxanthin ethanol solution, recorded as FX; Step 2, adding the exosome suspension extracted from the algae liquid cultured in the heterotrophic mode in Example 1 into PBS buffer to obtain a microalgae exosome solution with a final protein concentration of 1 mg / mL, recorded as EV; Step 3. Add the ethanol solution of fucoxanthin and the microalgae exosome solution to the cuvette in a mass ratio of 1:1 and incubate for 30 minutes. Then add 2 times the volume of the mixed solution of electroporation buffer (1.15mM potassium dihydrogen phosphate, 25mM potassium chloride, 1.46M sucrose, pH7.2, filtered through a 0.22μm filter) to increase the capacitance. Then use the BioRad electroporator to electroporate the mixed solution in the cuvette, control the voltage to 100-500V, and the capacitance to 300-700μF for electric shock. Then incubate at 37℃ for 1h to restore the EV membrane structure. Centrifuge the mixed solution at 100000g and 4℃ for 30min to remove the electroporation buffer and free FX. The precipitated particles are microalgae exosome-fucoxanthin composite nanoparticles, recorded as FX-EV. Figure 4 The loading efficiency statistics under different conditions show that as the voltage increases, the drug loading rate increases first and then decreases gradually. As the capacitance increases, the drug loading rate also shows similar results. Figure 4 It can be seen that under the conditions of voltage 200 V and capacitance 500 μF, the optimal fucoxanthin loading rate is 15.64±3.12%, so this electroporation condition was selected for subsequent experiments. The mass ratio of the above-mentioned fucoxanthin ethanol solution to the microalgae exosome solution can also be 0.5:1, 1.5:1, and any value within 0.5-1.5:1.

[0034] Structural characterization of the microalgae exosome-fucoxanthin composite nanoparticles prepared in Example 4 and Example 3.

[0035] 1. Transmission electron microscopy (TEM) determination: The morphological structure of the composite nanoparticles was observed using a JEM-2100 transmission electron microscope (TEM). The composite nanoparticles prepared in Example 3 were dissolved in PBS buffer and then dripped onto a carbon-coated copper grid. After standing at room temperature for 10 minutes, excess sample was removed with filter paper. The copper grid was then stained with phosphotungstic acid for 10 seconds and excess liquid was removed with filter paper. After washing with PBS buffer for 1 minute, excess liquid was removed with filter paper. The sample was dried under an incandescent lamp and the morphology of the newly prepared sample was observed using a transmission electron microscope. Figure 5 is a transmission electron microscopy image of FX-EV composite nanoparticles, such as Figure 5 As shown, the microalgae exosome-fucoxanthin composite nanoparticles are spherical core-shell nanoparticles, and fucoxanthin is adsorbed in the exosome lipid bilayer structure, which can prove the successful construction of the system.

[0036] 2. Particle size and zeta potential determination: After dissolving the exosome suspension extracted from the algae cultured in different modes in Example 1 and the microalgae exosome-fucoxanthin composite nanoparticles prepared in Example 3 in PBS buffer, the particle size and zeta potential of the samples to be tested were measured using a Malvern particle size analyzer. The purpose of dilution is to avoid the multiple scattering effect caused by the instrument. Each sample was measured three times and the results were averaged. The results are shown in Figure 2. Figure 6 shown.

[0037] Depend on Figure 6 It can be seen that the particle size of Chlorella FACHB-9 and the particle size and Zeta potential of FX-EV composite nanoparticles under different culture modes are consistent with the exosome particle size of 30 to 200 nm and the potential of -10 to -30 mV. It can be inferred that the particle size of Chlorella FACHB-9 may be positively proportional to the protein concentration. The particle size of exosomes extracted under heterotrophic, mixed and autotrophic modes increases with the increase of protein concentration. The particle size of FX-EV composite nanoparticles is the largest because the encapsulated fucoxanthin further increases the particle size of exosome protein.

[0038] Example 5. Determination of drug loading rate of microalgae exosome-fucoxanthin composite nanoparticles prepared in Example 3.

[0039] FX-EV composite nanoparticles were mixed with methanol in a volume ratio of 1:1, and then the FX-EV mixture was sonicated in an ice bath using a probe ultrasonic disruptor, set to 30% amplitude, on / off 5 / 10s, 50 cycles, and then centrifuged at 100000g for 30min at 4°C. The supernatant was taken after centrifugation and the concentration and mass of FX in FX-EV were determined by high performance liquid chromatography (HPLC). The whole experiment was protected from light. The chromatographic column was YMCC-30 (250×4.6 mm, 3 μm, Waters, Ireland), the mobile phase was: A was methanol, B was water, the detection wavelength was 450 nm, the flow rate was 0.7 μm / min, the detection wavelength was 450nm, the column temperature was 35°C, the injection volume was 10 μL, and the total elution time was 25 min. At the same time, the precipitate was collected, and the protein content of the precipitate was determined according to the BCA method in Example 1, which was the mass of EV in FX-EV.

[0040] The drug loading rate, entrapment rate, protein recovery rate, and fucoxanthin loss rate of FX-EV samples were calculated according to the following formulas.

[0041] Drug loading rate (%) = FX mass in FX-EV / total mass of FX-EV * 100%; Embedding rate (%) = FX concentration in FX-EV / total FX concentration * 100%, where the total FX concentration is the FX concentration in the mixed solution before electroporation in step 3 of Example 3; Protein recovery rate (%) = EV mass in FX-EV / total EV mass * 100%, where the total FX mass is the EV solution concentration in the mixed solution before electroporation in step 3 of Example 3 multiplied by the EV solution volume; Fucoxanthin loss rate (%) = 100% - FX encapsulation rate.

[0042] Figure 7 The statistical results of drug loading rate, embedding rate, protein recovery rate, and fucoxanthin loss rate of FX-EV composite nanoparticles are shown in Figure 2. Figure 7 As shown, the FX loading rate in FX-EV composite nanoparticles was 15.64±3.12%, the encapsulation rate was 87.03±2.82%, the protein recovery rate was 97.82±2.04%, and the fucoxanthin loss rate was 12.98±2.82%.

[0043] Example 6. Determination of the stability of the microalgae exosome-fucoxanthin composite nanoparticles prepared in Example 3.

[0044] 1. Photostability determination: FX was dissolved in methanol, and FX-EV composite nanoparticle samples were dissolved in PBS buffer, with a final concentration of 2 mg / mL. The samples were irradiated with 5 W, 352 nm ultraviolet light at 25 °C for 1, 2, 3, 4 and 5 h to determine photostability. Take 1 ml of sample every 1 h, set up three groups of parallels, and then use the method in Example 5 to determine the fucoxanthin content in the sample. The fucoxanthin retention rate is calculated as follows: Retention rate (%) = fucoxanthin content in samples at different treatment time points / original fucoxanthin content in untreated samples.

[0045] Figure 8 Figure a shows the effect of different time on the photostability of fucoxanthin under different conditions. After 5 h of UV irradiation, the retention rate of free FX was 14.01±1.14%, while the retention rate of FX in the FX-EV sample was 36.52±1.75%, which was significantly higher than that of free fucoxanthin, indicating that the construction of this system can effectively improve the photostability of fucoxanthin and overcome the instability of fucoxanthin under light conditions.

[0046] 2. Thermal stability determination: FX was dissolved in methanol and FX-EV composite nanoparticles were dissolved in PBS buffer, with a final concentration of 2 mg / mL. The samples were heated in a 60°C water bath for 30, 60, 90, 120, and 150 minutes, and 1 ml of sample was taken every 30 minutes. Three groups of parallels were set up, and then the fucoxanthin content in the samples was determined, and the fucoxanthin retention rate was further calculated using the above formula.

[0047] Figure 8 Figure b shows the effect of different time on the thermal stability of fucoxanthin under different conditions. After heating at 60°C for 150 min, the retention rate of free FX was 47.62±2.26%, while the retention rate of FX in the FX-EV sample was 63.27±1.84%, which was significantly higher than that of free fucoxanthin, indicating that the construction of this system can effectively improve the thermal stability of fucoxanthin and overcome the instability of fucoxanthin under heating conditions.

[0048] 3. Room temperature stability determination: FX was dissolved in methanol and FX-EV composite nanoparticle samples were dissolved in PBS buffer, with a final concentration of 2 mg / mL. The samples were stored in the dark at room temperature for 3, 6, 9, 12, and 15 days to determine the storage stability. 1 ml of sample was taken every 3 days, and three groups were set up in parallel. Then the fucoxanthin content in the sample was determined, and the fucoxanthin retention rate was further determined using the above formula.

[0049] Figure 8Figure c shows the effect of different storage times at room temperature on the stability of fucoxanthin under different conditions. After 12 days of storage at room temperature in the dark, the retention rate of free FX was 13.28±2.20%, while the retention rate of FX in the FX-EV sample was maintained at more than 70%, which was significantly higher than the retention rate of free fucoxanthin. This indicates that the construction of this system can effectively improve the storage stability of fucoxanthin and overcome the instability of fucoxanthin under long-term storage at room temperature. The above results show that the construction of the Chlorella exosome-fucoxanthin composite nanoparticle system can overcome the instability of fucoxanthin under light, heat, and room temperature storage, and the construction of this system can effectively improve the stability of fucoxanthin.

[0050] Example 7. Determination of the antioxidant activity of the microalgae exosome-fucoxanthin composite nanoparticles prepared in Example 3.

[0051] ABTS free radical scavenging experiment: Step 1: ABTS (2,2'-azino-bis-3-ethylbenzothiazoline-6-sulfonic acid) is oxidized to generate a relatively stable blue-green cationic radical ABTS. + , 7mM ABTS solution and 140mM potassium persulfate solution were mixed in equal volumes, and allowed to react for 12 hours at room temperature in the dark. The mixture was diluted with distilled water until the absorbance at 734nm was 0.7, to obtain ABTS working solution.

[0052] Step 2: Dissolve the FX-EV composite nanoparticles prepared in Example 3 in PBS buffer to obtain an FX-EV solution, so that the concentration of the loaded FX is 200 μg / mL, and the concentration of the wall material EV is 1 mg / mL. Take 50 μL of FX-EV solution, 50 μL of FX solution with a concentration of 200 μg / mL, and 50 μL of EV solution with a concentration of 1 mg / mL and mix with 150 μL of ABTS working solution as the experimental group Ai, replace the ABTS working solution with distilled water as the control group Aj, and replace the sample with distilled water as the blank group A0. At the same time, weigh 50 μL of Vc solution with a concentration of 200 μg / mL as a positive control. Add all group samples to a 96-well ELISA plate and react in the dark for 30 minutes. Set three groups in parallel. After the reaction, use an ELISA reader to measure the absorbance value (A) of the solution in each well at a wavelength of 734 nm.

[0053] Based on the measured absorbance value, the antioxidant content of ABTS・ + Clearance rate (%): ABTS clearance rate (%) = [1-(Ai-Aj) / A0]* 100%. Fig. 9From figure a, we can see that the ABTS free radical scavenging rates of FX and EV are 38.21±1.11% and 26.62±1.02%, respectively, while that of FX-EV is 50.58±1.05%. The synergistic effect between FX and EV in the FX-EV composite nanoparticles significantly improves the ABTS free radical scavenging rate of the composite nanoparticles.

[0054] 2. DPPH free radical scavenging experiment: DPPH (1,1-diphenyl-2-trinitrophenylhydrazine) is a stable free radical that is dark purple in ethanol solution and has a strong absorption peak at 517nm. When antioxidants are present, their lone pair electrons are paired, making the color of the DPPH free radical solution lighter and the absorbance lower. The ability of antioxidants to scavenge DPPH free radicals can be evaluated by measuring the change in absorbance.

[0055] The FX-EV composite nanoparticles prepared in Example 3 were dissolved in PBS buffer to obtain an FX-EV solution, so that the concentration of the loaded FX was 200 μg / mL and the concentration of the wall material EV was 1 mg / mL. 50 μL of FX-EV solution, 50 μL of FX solution with a concentration of 200 μg / mL, and 50 μL of EV solution with a concentration of 1 mg / mL were mixed with 0.5 mL of 0.2 mM DPPH ethanol solution as the experimental group Ai, and anhydrous ethanol was used instead of DPPH ethanol solution as the control group Aj, and distilled water was used instead of the sample as the blank group A0. 50 μL of Vc solution with a concentration of 200 μg / mL was weighed as a positive control, and all group samples were added to a 96-well ELISA plate to react in the dark for 30 minutes. Three groups were set in parallel. After the reaction, the absorbance value (A) of the solution in each well was measured at a wavelength of 517 nm using an ELISA instrument.

[0056] According to the measured absorbance value, the scavenging rate (%) of antioxidant substances on DPPH is calculated using the following formula: DPPH scavenging rate (%) = [1-(Ai-Aj) / A0]* 100%. Fig. 9 As shown in Figure b, the DPPH radical scavenging rates of FX and EV were 31.31±1.08% and 26.21±1.12%, respectively, while that of FX-EV was 44.48±1.04%. The synergistic effect between FX and EV in the FX-EV composite nanoparticles significantly improved the DPPH radical scavenging rate of the composite nanoparticles.

[0057] The above results show that the construction of Chlorella exosome-fucoxanthin composite nanoparticle system can effectively improve the bioavailability of fucoxanthin. The conjugated double bond system in the chemical structure of fucoxanthin itself makes it susceptible to oxidation and loses its activity. The encapsulation of exosomes can reduce the damage of these adverse factors to fucoxanthin, thereby maintaining its structural integrity and maintaining its antioxidant activity before reaching the site of action, which may enhance its ability to exert antioxidant effects in vivo. In addition, exosomes themselves contain some components with antioxidant activity, such as certain proteins, nucleic acids and lipids, which may produce a synergistic antioxidant effect when acting together with fucoxanthin.

[0058] The above description is not intended to limit the present invention, and the present invention is not limited to the above examples. Any changes, modifications, additions or substitutions made by a person skilled in the art within the spirit and scope of the present invention shall also fall within the protection scope of the present invention.

Claims

1. A method for preparing microalgae exosome-fucoxanthin composite nanoparticles, characterized in that The following steps are involved: The fucoxanthin ethanol solution and the microalgae exosome solution were added to the cuvette at a mass ratio of 0.5-1.5:1 and incubated for 30 minutes. Then, 1-3 times the volume of the mixed solution was added with an electroporation buffer. The mixed solution in the cuvette was electroporated using an electroporator. The voltage was controlled to be 100-500V and the capacitance was 300-700μF for electric shock. After incubation at 35-40°C for 0.5-2h, the mixed solution was centrifuged at 80000-120000g and 4°C for 20-40min, and the precipitated particles were collected to obtain microalgae exosome-fucoxanthin composite nanoparticles.

2. The method for preparing microalgae exosome-fucoxanthin composite nanoparticles according to claim 1, characterized in that The preparation method of the fucoxanthin ethanol solution is as follows: dissolve fucoxanthin in 95% ethanol, stir with a magnetic stirrer to completely dissolve it, and obtain a fucoxanthin ethanol solution with a concentration of 5 mg / mL.

3. The method for preparing microalgae exosome-fucoxanthin composite nanoparticles according to claim 1, characterized in that The preparation method of the microalgae exosome solution is as follows: the cultured Chlorella algae solution is centrifuged at 200-400g for 8-12min, 1500-2500g for 15-25min, and 8,000-12000g for 25-35min at 4°C by differential centrifugation to remove cells and cell debris, the supernatant is filtered through a 0.22μm water filter membrane and then ultracentrifuged at 80,000-1200,000g for 80-100min, the precipitate is resuspended in sterile PBS buffer to obtain a microalgae exosome solution with a final protein concentration of 1 mg / mL.

4. The method for preparing microalgae exosome-fucoxanthin composite nanoparticles according to claim 3, characterized in that The chlorella is cultured in an autotrophic mode, specifically as follows: a single colony of Chlorella sp FACHB-9 is inoculated into 200 mL of BG11 culture medium and cultured in a shaker at 25° C. and 120 rpm for 6-8 days, then the seed solution is continuously inoculated into 600 mL of BG11 culture medium and cultured in a shaker at 25° C. and 120 rpm for 5-6 days, and the chlorella FACHB-9 algae solution is collected, wherein the formula of the BG11 culture medium is as follows: NaNO3 1.5 g, K2HPO4 0.04 g, MgSO4·7H2O 0.075 g, CaCl2·2H2O0.036 g, Na2CO3 0.02 g, citric acid 0.006 g, ferric citrate 0.006 g, trace element solution A5 1 mL and distilled water 1000 mL, and the formula of the trace element solution A5 is: H3BO3 2.86g / L, MnCl2·4H2O 1.81g / L, ZnSO4 0.222g / L, Na2MoO4 0.39g / L, CuSO4·5H2O 0.079g / L, Co (NO3)2·6H2O 0.049g / L.

5. The method for preparing microalgae exosome-fucoxanthin composite nanoparticles according to claim 4, characterized in that The chlorella is cultured in a polyculture mode, specifically as follows: Chlorella spFACHB-9 The seed solution was inoculated into 200 mL of BG11 medium containing 2 g / L glucose and cultured in a shaker at 25°C and 120 rpm for 6-8 days. The seed solution was then inoculated into 600 mL of BG11 medium containing 2 g / L glucose and cultured in a shaker at 25°C and 120 rpm for 5-6 days to collect the Chlorella FACHB-9 algae solution.

6. The method for preparing microalgae exosome-fucoxanthin composite nanoparticles according to claim 3, characterized in that The chlorella is cultured in a heterotrophic mode, specifically as follows: Chlorella spFACHB-9 The seed solution was inoculated into 200 mL of modified Endo medium and cultured in a shaker at 25°C and 120 rpm for 6-8 days. The seed solution was then continuously inoculated into 600 mL of modified Endo medium and cultured in a shaker at 25°C and 120 rpm for 5-6 days. The algae solution of Chlorella FACHB-9 was collected. The formula of the modified Endo medium was as follows: 28 g / L glucose, 1.2 g / L potassium dihydrogen phosphate, 4.8 g / L urea, 1.2 g / L magnesium sulfate, 105 mg / L calcium chloride dihydrate, 16 g / L ferrous sulfate heptahydrate, 2.1 mg / L disodium ethylenediaminetetraacetic acid, 0.2 g / L trisodium citrate, 2.86 mg / L boric acid, 0.222 mg / L zinc sulfate heptahydrate, 1.81 mg / L manganese chloride tetrahydrate, 0.025 mg / L sodium molybdate, 0.07 mg / L copper sulfate pentahydrate and 1.2 mg / L cobalt nitrate hexahydrate.

7. The method for preparing microalgae exosome-fucoxanthin composite nanoparticles according to claim 1, characterized in that The formula of the electrotransfer buffer is as follows: 1.15 mM potassium dihydrogen phosphate, 25 mM potassium chloride, 1.46 M sucrose, pH 7.

2.

8. A method for preparing microalgae exosome-fucoxanthin composite nanoparticles according to any one of claims 1 to 4, characterized in that: The mass ratio of the fucoxanthin ethanol solution to the microalgae exosome solution is 1:

1.

9. Use of microalgae exosome-fucoxanthin composite nanoparticles prepared by the method of claim 8 in the preparation of antioxidants.

10. Use of microalgae exosome-fucoxanthin composite nanoparticles prepared by the method of claim 8 in the preparation of ABTS free radical scavenger and / or DPPH free radical scavenger.

Citation Information

Patent Citations

  • Preparation method of exosome capable of simultaneously loading chemical drug and nano-material

    CN108114290A

  • Exosome with diagnosis and treatment functions and preparation method of exosome

    CN109568269A

  • Microalgae exosome as well as preparation method and application thereof

    CN115992052A

  • Exosome ferroferric oxide nanoprobe as well as preparation method and application thereof

    CN116370656A

  • Application of probiotic vesicle-fucoxanthin composite nanoparticles in preparation of functional food and medicine for treating colitis

    CN116406792A